Update on protracted bacterial bronchitis in children - Xiao-bo Zhang; Xiao Wu; Guang-min Nong (BMC, 2020)
Abstract Background Chronic cough is a common symptom in children and protracted bacterial bronchitis (PBB) is one of the causes of chronic cough. However, the understanding of this disease remains limited. The present study aims to update PBB in children. Methods The clinical data of children with PBB from 2014 to 2018 were retrospectively analyzed, and PBB clinical features of published studies were summarized. Electronic databases were searched in May 2019. Clinical studies were included in the present study. Reviews were undertaken in duplicate. Results Totally 712 cases were analyzed in this study, including 52 cases in our center and 660 cases from 14 studies. In the 52 cases, 88.5% of patients with PBB were less than 6 years old and all of them complained of wet cough. Three cases were confirmed with laryngomalacia, and microbiologically-based-PBB were identified in 13 cases (9 Streptococcus pneumonia, 3 Staphylococcus aureus, and 1 Pseudomonas aeruginosa). Twenty cases were completely remitted after treatment. In the 14 studies, the patients with PBB were typically younger than 3 years old, accompanying wheezing and airway malacia. Co-infection was common in most western cases, Streptococcus pneumonia, Haemophilus influenza and Moraxella catarrhalis were the top three pathogens. Symptoms were improved in most patients, whereas some cases with comorbidities required prolonged antibiotics treatment. Conclusions PBB is common in male infants with chronic wet cough and accompanied by wheezing and airway deformities. Most cases are clinically diagnosed PBB in China and microbiologically-based-PBB is common in western countries. Co-infection could be found, Streptococcus pneumoniae and Haemophilus influenza were the most frequent etiology in China and western countries, respectively. Patients with comorbidities may need extended antibiotics treatment for more than 2 weeks.